Quasi-Isothermal External Short Circuit Tests Applied to Lithium-Ion Cells: Part I. Measurements. Issue 14 (1st January 2018) - Rheinfeld, Alexander; Noel, Andreas; Wilhelm, Jörn; Kriston, Akos; Pfrang, Andreas; Jossen, Andreas
Abstract : Single-layered pouch-type cells were exposed to quasi-isothermal external short circuit tests to study the influence of electrode loading and tab configuration on the short circuit characteristics. Additionally, test conditions such as initial cell temperature, cell voltage and external short circuit resistance were varied. Keeping the cell's temperature increase below 1°C whilst using a calibrated calorimetric setup, a direct correlation between the electrical and thermal behavior could be shown without occurring exothermal side reactions. Previously studied step-like characteristics in the transient current profile could be confirmed for all cells and test conditions, showing differing durations and magnitudes of the observed plateaus based on ohmic resistances, transport processes and reaction kinetics. Lower electrode loadings, counter-tab configurations homogenizing the current density distribution and higher initial cell temperatures accelerate the short circuit by increasing the cell current due to a reduced effective cell resistance. Whilst the chosen initial cell voltages and external short circuit resistances showed a minor impact on the short circuit dynamics, the initial state of charge revealed a noticeable influence defining the discharged capacity and the amount of generated heat. By post mortem analysis, the observed over-discharge could be correlated to an anodic dissolution of the negative electrode's copper current collector.